To establish the prevalence of eating disorders and compare effectiveness of treatment of eating disorders in Kelantan students - Zain, Azhar (2001)
This paper describes the development of a Malay version self-report questionnaire designed to assess assumptions and beliefs associated with eating disorders.Factor analyses suggested a replicable four factor structure consisting of the following dimensions: negative self-beliefs; weight and shape as a means to acceptance by others; weight and shape as a means to self-acceptance;and control over eating.The subscales possess good psychometric properties and significant correlations were found between the subscales and other measures of the specific and general psychopathology of eating disorders.The questionnaire also distinguished two groups of patients with eating disorders from normal controls.The usefulness of the measure and implications of the findings for cognitive theories of eating disorders are briefly discussed.